2022
DOI: 10.1111/ajgw.12544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of phenology, growth characteristics and berry composition in a hot Australian climate to identify wine cultivars adapted to climate change

Abstract: Background and Aims: The phenology, growth traits and fruit composition of cultivars in the CSIRO germplasm collection, located in a hot Australian region, were assessed to identify those adapted to climate change. Methods and Results: The study involved 465 cultivars assessed over four seasons. Differences in key traits included a 5-week range in budburst; a 4-month harvest window; a twofold difference in the growth period from budburst to harvest; a fivefold difference in fruitfulness and in leaf area index;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Of the remaining cultivars, Ehrenfelser and Reichensteiner produced smaller vines than Egiodola or Perdea. The low‐vigour classification of the scion cultivars has recently been confirmed based on leaf area index (LAI) of own‐rooted vines in the CSIRO collection (Clingeleffer and Davis 2022). In that study the relative difference between the cultivars was also maintained, except that the LAI of Egiodola or Perdea were similar to Roussanne.…”
Section: Discussionmentioning
confidence: 97%
“…Of the remaining cultivars, Ehrenfelser and Reichensteiner produced smaller vines than Egiodola or Perdea. The low‐vigour classification of the scion cultivars has recently been confirmed based on leaf area index (LAI) of own‐rooted vines in the CSIRO collection (Clingeleffer and Davis 2022). In that study the relative difference between the cultivars was also maintained, except that the LAI of Egiodola or Perdea were similar to Roussanne.…”
Section: Discussionmentioning
confidence: 97%
“…In the late ripening 2006 season, despite the low TSS, a high pH was recorded. Clingelefer and Davis [4] found that cultivars with delayed ripening and low TSS tended to have high pH. In contrast, the signifcant efect of cane number on pH was highly correlated with both TSS (r � 0.97) and yield (r � −0.99), the latter being highly correlated with TSS (−0.93).…”
Section: Ripening and Fruitmentioning
confidence: 98%
“…For Sultana, nodes 7-10 tended to be the most fruitful, whereas for Sunmuscat, nodes 6-16 tended to potentially be highly fruitful but also impacted by cane number treatment. Te relatively high fruitfulness of basal nodes (0.7-1.2 bunches per shoot), depending on season, indicates that Sunmuscat could be spur pruned for table grape production or mechanically hedged for wine production [4] as the values were similar to those reported for a range of table grape and wine cultivars [37]. Te changes in fruitfulness attributed to lighter pruning over time showed that the 6 cane treatment had higher fruitfulness at most node positions in the third season than other treatments (Figures 2 and 3).…”
Section: Patterns Of Budburst and Fruitfulness Along The Canementioning
confidence: 99%
See 1 more Smart Citation
“…This is exacerbated by the fact that many of the imported European cultivars currently grown in Australia originate from cooler climates and are not adapted to such temperature extremes (Venios et al 2020). Cultivars that have been selected over centuries to be productive in warm to hot and arid regions of Greece, Portugal and Spain are likely to be more tolerant to heat and should be evaluated under Australian conditions (Gransden 2019, Clingeleffer and Davis 2022). Many of these cultivars, however, have other limitations such as sensitivity to disease or lower wine quality that may limit their future adoption.…”
Section: Future Opportunities/challengesmentioning
confidence: 99%